Perlindungan Hukum Bagi Pihak Yang Mengalami Cacat Kehendak Dalam Proses Pembuatan Perjanjian Bisnis - Handri, Handri Raharjo (Asosiasi Ahli Administrasi Indonesia, 2021)
The business world is now growing very rapidly. On that basis, many people later switched professions to become business people. On the other hand, many novice businessmen have actually suffered losses due to the business agreement they made not in accordance with the provisions. One of them seems to contain elements of a defect of consent. This is where the law provides protection. In connection with this protection, the problem that becomes the focus of the study is what is the form of defect of consent and legal protection for parties who have a defect of consent in a business agreement. The research method used is the legal research method with the type of normative legal research. The type of data used is the type of secondary data obtained through library research. Furthermore, after all the data obtained from the results of this literature research have been collected completely and have been systematically compiled, then processed and analyzed using qualitative data analysis methods. Based on Article 1320 of the Civil Code, it is stated that the terms of the validity of the agreement include agreement, skill, certain matters and lawful causes. In relation to this agreement, the consensus must be given in an independent state and authority. In it there must be no defect of consent which include an oversight (dwaling); coercion (dwang or bedreiging); and deception (bedrog). The form of legal protection for parties who have a defect of consent in a business agreement is that they can file an agreement cancellation through litigation, namely the court on the basis of non-fulfillment of the subjective terms of the agreement.